User Satisfaction Analysis of QGIS and CarryMap Using End User Computing Statisfaction and User Centered Design Methods - Ira Zulfa; Richasanty Septima; Rapiah Rapiah; Muhamad Yustisar (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
Using End User Computing Satisfaction (EUCS) and User Centered Design (UCD) methods, this study investigated user satisfaction with QGIS and CarryMap. The research objective was to deploy elements such as content, accuracy, ease of use, and timeliness. A survey of students and teachers showed that users were more satisfied with the latest versions of both applications. The findings show that the user interface and functionality have evolved, which indicates the direction of future development of mapping applications.